Advertisements promoting HPV vaccine for adolescent males: Does source matter? - Pepper, Jessica K. (2012)
OBJECTIVES: Many parents recall hearing of HPV vaccine through drug company advertisements. We sought to examine whether parents accurately recall the source (i.e., sponsor) of ads promoting HPV vaccine and the impact of drug company ads. METHODS: A U.S. national sample of 544 parents of adolescent males ages 11–17 participated in an online between-subjects experiment. Parents viewed an advertisement encouraging HPV vaccination for boys with a logo from a randomly assigned source. Parents rated trust, likability, and motivation for vaccination while viewing the ad and later indicated who they believed sponsored it. RESULTS: Nearly half (43%) of parents who viewed a hypothetical advertisement containing a logo incorrectly identified the ad source. More parents correctly identified the source of drug company ads than ads from other sources (62% vs. 25%, OR 4.93, 95% CI 3.26–7.46). The majority of parents who saw a logo-free ad believed a drug company created it (60%). Among parents who correctly identified the ad source, drug company ads decreased motivation to vaccinate their sons, an association mediated by reduced liking of and trust in the ads. CONCLUSIONS: Parents were more accurate in identifying drug company ads, primarily because they tended to assume any ad was from a drug company. Public health organizations may need to take special measures to ensure their messages are not perceived as sponsored by drug companies.